2007
DOI: 10.1086/521301
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Anisotropies in the Cosmic Far-Infrared Background Detected by the Multiband Imaging Photometer for Spitzer : Constraint on the Bias

Abstract: We report the detection of correlated anisotropies in the Cosmic Far-Infrared Background at 160 µm. We measure the power spectrum in the Spitzer/SWIRE Lockman Hole field. It reveals unambiguously a strong excess above cirrus and Poisson contributions, at spatial scales between 5 and 30 arcminutes, interpreted as the signature of infrared galaxy clustering. Using our model of infrared galaxy evolution we derive a linear bias b = 1.74 ± 0.16. It is a factor 2 higher than the bias measured for the local IRAS gala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
116
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(132 citation statements)
references
References 30 publications
15
116
1
Order By: Relevance
“…Those values are consistent with the linear bias derived in work of Lagache et al (2007), which was measured from cosmic farinfrared background anisotropies at 160 μm (b = 1.74 ± 0.16). Both measurements probe similar redshift range (z Lagache ∼ 1); -the sample at 0.9 < z ≤ 1.3, composed of brighter galaxies (L TIR ∼ 10 11.84 L ), seems to be residing in lower minimal mass DMH (M h < 10 12 M h −1 ) than the lower luminosity (with L TIR ∼ 10 11.15 L and M h > 10 12 M h −1 ) galaxies at 0.5 < z ≤ 0.9.…”
Section: Discussionsupporting
confidence: 92%
“…Those values are consistent with the linear bias derived in work of Lagache et al (2007), which was measured from cosmic farinfrared background anisotropies at 160 μm (b = 1.74 ± 0.16). Both measurements probe similar redshift range (z Lagache ∼ 1); -the sample at 0.9 < z ≤ 1.3, composed of brighter galaxies (L TIR ∼ 10 11.84 L ), seems to be residing in lower minimal mass DMH (M h < 10 12 M h −1 ) than the lower luminosity (with L TIR ∼ 10 11.15 L and M h > 10 12 M h −1 ) galaxies at 0.5 < z ≤ 0.9.…”
Section: Discussionsupporting
confidence: 92%
“…The catalogs and maps were created for different levels of bias between the fluctuations of infrared galaxy emissivities and the dark matter density field. We use a bias b = 1.5, which is very close to that measured by Lagache et al (2007).…”
Section: Introductionmentioning
confidence: 94%
“…Alternatively, the infrared background anisotropies could also provide information about the correlation between the sources of the CIB and dark matter (Haiman & Knox 2000;Knox et al 2001;Amblard & Cooray 2007), and its redshift evolution. Lagache et al (2007) and Viero et al (2009) reported the detection of a correlated component in the background anisotropies using Spitzer/MIPS (160 μm) and BLAST (250,350, and 500 μm) data. These authors found that star formation is highly biased at z > 0.8.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1a) contains contributions from spatial variations in Galactic dust clouds, or cirrus, brightness at large angular scales, the clustering of galaxies at intermediate angular scales, and a white-noise component at small angular scales arising from the Poisson behavior of the faint galaxies 7,9 . The cirrus signal in our Lockman-SWIRE field is taken from existing measurements in the same field with IRAS 100 µm and MIPS 22 and extend this spectrum from 100 µm to SPIRE wavelengths using the spectral dependence of a Galactic dust model 23 . We remove this cirrus power spectrum from our measurements and account for the uncertainty of the cirrus power spectrum by adding its error in quadrature to errors of our power spectrum points.…”
mentioning
confidence: 99%